THE INTERPLAY OF EFFECT OF FAW GAME AND PSYCHOLOGICAL BEHAVIOUR STUDENTS’ IN LEARNING VOCABULARY - Uceng, Andi; Sadapotto, Andi (Uniqbu Journal of Social Sciences, 2022)
The purpose of this study was to determine whether the use of FAW games in vocabulary learning could influence the behavior of students’ psychiatology. In this study, researchers focused on aspects of students’ interests and attitudes. This study used a qualitative research method, the population of this study was seventh grade students of SMP N 2 Baranti in the years 2018-2019. The total population is 101 students consisting of four classes. Class VII1 was taken as a sample using a cluster sampling technique, the total number of samples was 25. The instruments used in this study were questionnaires of interest and attitude. The results of this study indicate that students’ interest in using FAW game method is quite high, students feel more relaxed in learning so that their understanding of vocabulary increases. Besides that students’ attitudes in vocabulary learning using the FAW game method show good things, students are more active and cooperate with other students. This shows that H1 is accepted. Based on the results of the interest questionnaire list, 16 students (64%) were very interested in the FAW game method and based on the results of the attitude questionnaire 19 students (76%) showed good attitude.